EKSISTENSI TARI LENGGER LAUT KARYA OTNIEL TASMAN - Pemiluwati, Umi Dwi; Bisri, Moh. Hasan (Universitas Negeri Semarang, 2020)
The Lengger Laut dance has been staged in several events abroad and in the country, one of the performances abroad in Desingel Belgium in the Europalia Festival on October 18, 2017. One of the performances performed in the country is at the Managing Arts Grant on the 29th August 2014 in Surakarta, the 2015 Helatari performance at the Salihara Theater building in Jakarta. The purpose of this study was to determine the existence of the Lengger Laut dance by Otniel Tasman. The Lengger Laut dance was created by a young photographer from Banyumas named Otniel Tasman. This study uses a qualitative descriptive approach, ethical and emic approaches, and structural and functional approaches. Data collection techniques obtained from observation, interviews and documentation. The technique of analyzing data uses data reduction, data presentation, draw conclusions. The data validity technique is carried out by triangulation of sources, technical triangulation and time triangulation. The results showed that the existence of the Sea Lengger Dance still exists, proven by the function of the show and the spread of the development of the Sea Lengger dance performance. Lengger Laut dance is included in contemporary dance nuances of Banyumas popular tradition that has been developed following the times. The Lengger Laut dance by Otniel Tasman has elements of the performance consisting of motion, performer, accompaniment or music, theme, fashion or costume, make-up, venue or stage, lighting and sound system. The Lengger Laut dance also functions as entertainment and as a performance or spectacle. Keywords: Existence, Lengger Laut Dance, performance